Balanites aegyptiaca leaf extract-mediated synthesis of silver nanoparticles and their catalytic dye degradation and antifungal efficacy - Dhaka, Anita; Raj, Shani; Githala, Chanda kumari; Chand Mali, Suresh; Trivedi, Rohini (Frontiers in Bioengineering and Biotechnology, 2022)
In this work, the biosynthesis of silver nanoparticles (AgNPs) is achieved using Balanites aegyptiaca (B. aegyptiaca) leaf extract. The biosynthesized AgNPs were characterized using UV-Vis spectrophotometer, Fourier transform infrared spectroscopy (FTIR), Dynamic light scattering (DLS), X-ray diffraction (XRD), Raman spectroscopy, Transmission electron microscopy (TEM) and Scanning electron microscopy with (SEM-EDS). The AgNPs produced have an average size in the range of 10–20 nm and are spherical in shape and crystalline in nature. The application of synthesized AgNPs to dye degradation was investigated. The results show that the use of AgNPs removed the two organic pollutants methylene blue (MB) and congo red (CR) (93.47%) and (78.57%), respectively. The in vitro antifungal activity against Fusarium oxysporum, a phytopathogenic fungus, was also evaluated. The maximum percent inhibition of radial growth was found to be 82.001.00% and the percent inhibition of spores to be 73.663.94 at 150g/ml of biosynthesized AgNPs.